2012
DOI: 10.1128/mcb.06541-11
|View full text |Cite
|
Sign up to set email alerts
|

ADAP Regulates Cell Cycle Progression of T Cells via Control of Cyclin E and Cdk2 Expression through Two Distinct CARMA1-Dependent Signaling Pathways

Abstract: T lymphocyte activation requires physical contact with an antigen-presenting cell and the propagation of signals from the antigen-specific T cell receptor (TCR) that result in proliferation and differentiation. Adapter proteins coordinate the assembly of signalosomes that are essential for optimal T cell activation (36). In T cells, adhesion and degranulation-promoting adapter protein (ADAP) positively regulates T cell receptor signaling by facilitating the activation of integrin receptors that enhances T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The ADAP-SKAP55 signaling module is critical for TCR-mediated activation of integrin-mediated adhesion with APCs (12, 13). A second pool of ADAP is not associated with SKAP55, but activates NF-κB and JNK in a TCR-inducible manner (12, 1416). …”
Section: Introductionmentioning
confidence: 99%
“…The ADAP-SKAP55 signaling module is critical for TCR-mediated activation of integrin-mediated adhesion with APCs (12, 13). A second pool of ADAP is not associated with SKAP55, but activates NF-κB and JNK in a TCR-inducible manner (12, 1416). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have established that PDK1 is critical for efficient activation of PKCθ in T cells and PKCβ in B cells by the PI3K pathway. PDK1 is also required for the subsequent assembly of the CBM complex to activate NF-κB during coordinated stimulation of the TCR and co-stimulatory receptor CD28 or during activation of the BCR [57][58][59]. PDK1 phosphorylates PKCθ and has a dual role in TCR-mediating NF-κB activation by recruiting PKCθ and CARMA1 into lipid rafts [60].…”
Section: Pkcθ and Pkcβmentioning
confidence: 99%
“…Using B-cell specific conditional PDK1 knock-out mice (Table 1) and chemical inhibitor approaches, it was demonstrated that PDK1 plays a critical role in B-cells by promoting transduction of the BCR signalings that are essential for the activation of both NF-κB and Foxo transcription factors. PDK1 is required for the survival of resting and activated B cells through the activation of Foxo and NF-κB respectively [57].…”
Section: Pkcθ and Pkcβmentioning
confidence: 99%
“…ADAP positively regulates both T-APC interactions and NF-κB and JNK transcriptional pathways (9, 1317). A fraction of ADAP is constitutively associated with Src kinase-associated phosphoprotein of 55 kDa (SKAP55) (18).…”
Section: Introductionmentioning
confidence: 99%
“…ADAP not associated with SKAP55 positively regulates the activation of NF-κB and JNK in a TCR-inducible manner (1518). The downstream effects of TCR-inducible interactions of ADAP with caspase recruitment domain (CARD) membrane-associated guanylate kinase (MAGUK) protein 1 (CARMA-1) and, transforming growth factor-β (TGF-β)-activated protein kinase (TAK-1) promote T cell entry into the cell cycle (9, 1517). The ADAP-CARMA-1-TAK-1 signalosome is also required for cytokine and chemokine production by NK cells after NKG2D or CD137 stimulation (20).…”
Section: Introductionmentioning
confidence: 99%